Pemberdayaan Perempuan Kampung Yensawai Melalui Pengolahan Tanaman Obat Keluarga di Pulau Batanta, Raja Ampat - Rachel Kamilia Faradiba Nibal; Rifki Elindawati; Hana Novia; Savero Seisa Mubin; Zahra Malikah Putri Ilham (Universitas Malikussaleh, 2026)
The high prevalence of hypertension and hypercholesterolemia risks among residents of Yensawai Village, Batanta Island, Raja Ampat, driven by high seafood consumption and limited intake of green vegetables, highlights the need for community-based preventive health interventions. To address this challenge, Asa Tanpa Batas, in collaboration with the Department of Political Science at Universitas Malikussaleh, implemented a women's empowerment initiative through the “Eastern Expedition” (Ekspedisi Kembara Timur) program, focusing on the utilization of Family Medicinal Plants (TOGA). The program engaged 15 indigenous women from the Marandan Weser tribe through a participatory approach consisting of field observation, group discussions, and interactive workshops. Training activities emphasized the hygienic processing of local medicinal plants and spices, including ginger, sappan wood, cloves, cinnamon, nutmeg leaves, and lemongrass, to support the prevention of metabolic diseases. The results demonstrated an improvement in participants’ knowledge and practical skills in processing and utilizing medicinal plants as part of daily health practices. The program successfully strengthened community-based health self-reliance while enhancing the capacity of indigenous women to serve as agents of change in promoting sustainable health resilience and community well-being in remote areas of Southwest Papua, Indonesia.